2021
DOI: 10.1097/mao.0000000000003157
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Preservation Techniques for Bone-Anchored Hearing Aid Surgery

Abstract: Objective:Compare outcomes of surgical techniques in percutaneous bone-anchored hearing implant surgery.Study Design:Matched retrospective cohort study.Setting:Tertiary referral center.Patients:Electronic review of adult and pediatric patients who underwent bone conduction device surgery by either the Minimally-invasive Ponto Surgery (MIPS) technique or the linear incision with no soft tissue removal (LnSTR) technique or between August 2015 and April 2018 at our facility.Intervention:Patients in MIPS group und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Subsequent studies comparing the MIPS technique to the LITT-P showed similar favorable outcomes, even with longer follow-up, regarding soft tissue reactions (27)(28)(29)(30)(31)(32)(33). Moreover, a shorter surgical time (27)(28)(29)(30)(31)(32)(33), better cosmetic appearance (28,29), and improved sensibility (28) were reported in favor of the MIPS technique compared with the LITT-P approach. However, implant loss was mentioned as a concern after the MIPS procedure with a couple of studies showing nonsignificantly more implant extrusion (28,29).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Subsequent studies comparing the MIPS technique to the LITT-P showed similar favorable outcomes, even with longer follow-up, regarding soft tissue reactions (27)(28)(29)(30)(31)(32)(33). Moreover, a shorter surgical time (27)(28)(29)(30)(31)(32)(33), better cosmetic appearance (28,29), and improved sensibility (28) were reported in favor of the MIPS technique compared with the LITT-P approach. However, implant loss was mentioned as a concern after the MIPS procedure with a couple of studies showing nonsignificantly more implant extrusion (28,29).…”
Section: Introductionmentioning
confidence: 91%
“…Also, there was an implant survival rate of >95% at the 20-week follow-up (26). Subsequent studies comparing the MIPS technique to the LITT-P showed similar favorable outcomes, even with longer follow-up, regarding soft tissue reactions (27)(28)(29)(30)(31)(32)(33). Moreover, a shorter surgical time (27)(28)(29)(30)(31)(32)(33), better cosmetic appearance (28,29), and improved sensibility (28) were reported in favor of the MIPS technique compared with the LITT-P approach.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition to providing benefits to patients, improvements in clinical efficiency using MIPS have been reported in cost analysis studies ( 32 ). While several studies have reported comparable implant survival rates for MIPS compared to LITT-P ( 27 29 , 31 , 33 ), lower implant survival for MIPS has also been reported ( 25 , 26 , 34 ). Possible reasons can be the reduced visibility during the procedure, introducing a potential risk of angulated insertion or interposing soft tissue.…”
Section: Introductionmentioning
confidence: 96%
“…The results of the MIPS technique are encouraging, and several recent studies have compared the clinical outcome of MIPS with that of the commonly used LITT-P ( 25 29 ). While both techniques show favorable soft tissue outcomes compared with the outcomes of previous tissue reduction approaches, MIPS is also associated with improvements in terms of surgery time, cosmetics and preservation of skin sensibility ( 25 31 ). In addition to providing benefits to patients, improvements in clinical efficiency using MIPS have been reported in cost analysis studies ( 32 ).…”
Section: Introductionmentioning
confidence: 99%